Short-term in situ shading effectively mitigates linear progression of coral-killing sponge Terpios hoshinota. - Thangadurai Thinesh; Ramu Meenatchi; Ramasamy Pasiyappazham; Polpass Arul Jose; Muthamizh Selvan; George Seghal Kiran; Joseph Selvin (PLoS ONE)
The coral-killing sponge, Terpios hoshinota is a global invasive species that has conquered coral patches within a short span of time, which has led to a significant decline in living coral cover at various geographical locations. In this study, we surveyed the linear progression and impact of the Terpios invasion on live coral patches along Palk Bay, Indian Ocean, from August 2013 to August 2015. The field inventory revealed an extensive fatality rate of 76% as a result of Terpios outbreak. Experimental findings showed that symbiotic cyanobacteria act as a nutritional factory for the aggressive growth of Terpios. Shading hypothetically impairs the nutritional symbiont of the invasive species: the effect of sunlight on cyanobacterial biomass and its influence on Terpios progression over live coral patches was tested through in situ shading experiments. This study showed that artificial shading with cotton fabric could effectively mitigate sponge growth on live coral without affecting coral homeostasis.